The Soft Tissue Changes Following Orthodontic Treatment of Bimaxillary Protrusion (A Clinical and Photographical Study) - Arkan Muslim; Hayder A Kadhim (College of Dentistry/ University of Baghdad, 2016)
Background: Bimaxillary protrusion is considered as one of the most important causes to seek the orthodontic treatment to get better esthetics. This study aimed to test the effect of orthodontic treatment in improvement the facial esthetics. Materials and Methods: Ten Iraqi Arab females having bimaxillary protrusion based on Class I malocclusions treated with fixed orthodontic appliance and extraction of the maxillary and mandibular 1st permanent premolars. Pre and post-treatment facial profile photographs were taken for each patients and the effect of treatment was tested in comparison with the pre-treatment photographs by using seven angular measurements. Results: After treatment, the upper and lower lip projections were decreased significantly, the naso-labial and mento-labial angles were increased significantly. Conclusion: Treatment of bimaxillary protrusion with fixed orthodontic appliances and extraction of four premolars improve the facial esthetics of the patients by decreasing the lip projection and increasing the naso-labial and mento-labial angles. Key words: Bimaxillary protrusion, facial esthetics, photographs.